2008
DOI: 10.1016/j.econlet.2007.09.030
|View full text |Cite
|
Sign up to set email alerts
|

The retirement consumption conundrum: Evidence from a consumption survey

Abstract: The Center for Retirement Research at Boston College, part of a consortium that includes a parallel centers at the University of Michigan and the National Bureau of Economic Research, was established in 1998 through a grant from the Social Security Administration. The goals of the Center are to promote research on retirement issues, to transmit new findings to the policy community and the public, to help train new scholars, and to broaden access to valuable data sources. Through these initiatives, the Center h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 20 publications
5
49
1
Order By: Relevance
“…In contrast to some of the earlier studies which found significant reductions in food expenditures at the time of retirement, recent literature has looked at broader consumption measures than just food expenditures and found, consistent with the standard life-cycle model, no significant consumption drop (see, e.g., Fisher et al (2008), Aguila et al (2011)). For the great majority of households, expenditures on food constitute a relatively small share of household budgets, and the relevance of changes in specific expenditure components for testing the life-cycle model seems questionable.…”
Section: Introductionmentioning
confidence: 41%
“…In contrast to some of the earlier studies which found significant reductions in food expenditures at the time of retirement, recent literature has looked at broader consumption measures than just food expenditures and found, consistent with the standard life-cycle model, no significant consumption drop (see, e.g., Fisher et al (2008), Aguila et al (2011)). For the great majority of households, expenditures on food constitute a relatively small share of household budgets, and the relevance of changes in specific expenditure components for testing the life-cycle model seems questionable.…”
Section: Introductionmentioning
confidence: 41%
“…Most of the literature on the relation between (male) retirement and consumption relates to the United States (see, for instance, Hamermesh, 1984;Aguiar and Hurst, 2013;Fisher et al, 2008;Lundberg et al, 2003) or the United Kingdom (see for example, Banks et al, 1998) or Italy (Battistin et al, 2009;Miniaci et al, 2010). It seems relevant to study the effect of retirement on household consumption in France, which is characterized by different earnings profiles and retirement institutions than the UK, the USA or Italy.…”
Section: Introductionmentioning
confidence: 99%
“…3 This phenomenon has been used lately to explain why consumption appears to drop upon retirement. It turns out that when flows of consumption from homes are included, this drop may be smaller than previously thought (Fisher, Johnson, Marchand, Smeeding, and Torrey 2005). 4 This use of a homogeneous form of value has been one strategy used to circumvent in capital theory problems associated with multiple produced means of production.…”
Section: Notesmentioning
confidence: 92%